2011
DOI: 10.5551/jat.5553
|View full text |Cite
|
Sign up to set email alerts
|

Statin Treatment Decreased Serum Asymmetric Dimethylarginine (ADMA) Levels in Ischemic Stroke Patients

Abstract: Aim: It remains unclear whether the decrease in the ADMA level associated with statin treatment results from the LDL-C-lowering effect or the pleiotropic effects of statins. A prospective, controlled study was conducted to examine whether statin treatment affects serum ADMA concentrations in ischemic stroke patients. Methods: Consecutive outpatients with non-cardiogenic ischemic stroke who had never been treated with statins and whose LDL-cholesterol level was higher than 140 mg/dL were enrolled and compared w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
24
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 31 publications
2
24
1
Order By: Relevance
“…Oxidative stress induces the expression of inflammatory genes and thereby enhances atherosclerotic processes 10,11) . Recently, ADMA levels have been shown to be decreased in patients in the chronic stage after ischemic stroke at least 3 months after the event when treated with statins in comparison to the non-statintreated group 12) . In another study, treatment with statins resulted in a significant reduction of markers of oxidative stress 13) .…”
mentioning
confidence: 99%
“…Oxidative stress induces the expression of inflammatory genes and thereby enhances atherosclerotic processes 10,11) . Recently, ADMA levels have been shown to be decreased in patients in the chronic stage after ischemic stroke at least 3 months after the event when treated with statins in comparison to the non-statintreated group 12) . In another study, treatment with statins resulted in a significant reduction of markers of oxidative stress 13) .…”
mentioning
confidence: 99%
“…In a subanalysis of our current study, in patients who were pretreated with statins or in whom treatment was initiated within the first week after the event (n=29), ADMA levels (day 1 to day 7) were not different compared with the nonstatin-treated patients (n=61; Mann-Whitney U test, P>0.05). This might be because of the fact that Nishiyama et al 5 included patients in the chronic stage ≥3 months after stroke, whereas our study investigated patients with hyperacute stroke. Therefore, in our study, dynamics in ADMA levels, which take place within the first days after the event of stroke, might overlap with any effects from pretreatment with statins.…”
mentioning
confidence: 54%
“…2 Kurtoglu et al 1 also emphasized the importance of statin treatment for ADMA levels in ischemic stroke. Nishiyama et al 5 observed a significant decrease in ADMA levels in 56 patients who were treated with statins for the first time during a period of 90 days beginning ≥3 months after ischemic stroke. In a subanalysis of our current study, in patients who were pretreated with statins or in whom treatment was initiated within the first week after the event (n=29), ADMA levels (day 1 to day 7) were not different compared with the nonstatin-treated patients (n=61; Mann-Whitney U test, P>0.05).…”
mentioning
confidence: 99%
“…2 The independent association between occurrence of stroke and chronic kidney disease has now been reported in several studies. 3 In a previous study that aimed to assess the effect of mildly reduced renal function on ADMA levels in age-matched patients with and without coronary artery disease documented by coronary angiography, it was shown that even a mild reduction in glomerular filtration rate was associated with an increased plasma level of ADMA.…”
Section: To the Editormentioning
confidence: 99%